The neurokinin-1 receptor mediates escalated alcohol intake induced by multiple drinking models. (15th July 2018) - Sequeira, Michelle K.; Nelson, Britta S.; Fulenwider, Hannah D.; King, Courtney E.; Nennig, Sadie E.; Bohannon, Jennifer B.; Cheng, Kejun; Rice, Kenner C.; Heilig, Markus; Schank, Jesse R.
Abstract: We have previously demonstrated that the neurokinin-1 receptor (NK1R) is upregulated in the central nucleus of the amygdala of alcohol preferring (P) rats and that this receptor mediates escalated alcohol consumption in this strain. However, it is unclear if non-genetic models of escalated consumption are also mediated by NK1R signaling, and if so, what brain regions govern this effect. In the experiments presented here, we use two methods of inducing escalated alcohol intake in outbred Wistar rats: yohimbine pretreatment and intermittent alcohol access (Monday, Wednesday, and Friday availability; 20% alcohol). We found that escalated alcohol consumption induced by both yohimbine injection and intermittent access is attenuated by systemic administration of the NK1R antagonist L822429. Also, when compared to continuous alcohol access or access to water alone, NK1R expression was increased in the nucleus accumbens (NAC) and dorsal striatum, but not the amygdala. Escalated consumption induced by intermittent access was attenuated when the NK1R antagonist L822429 was infused directly into the dorsal striatum, but not when infused into the NAC. Taken together, these results suggest that NK1R upregulation contributes to escalated alcohol consumption that is induced by genetic selection, yohimbine injection, and intermittent access. However there is a dissociation between the regions involved in these behaviors with amygdalar upregulation contributing to genetic predisposition to escalated consumption and striatal upregulation driving escalation that is induced by environmental exposures. Highlights: NK1R antagonism attenuates yohimbine-induced escalation in alcohol intake. NK1R antagonism attenuates alcohol intake on intermittent access. NK1R expression in the striatum upregulated by intermittent alcohol access. NK1R antagonism in dorsal striatum attenuates alcohol intake.